Preliminary studies of rubber toughened polypropylene - kenaf fiber composite - H. H. , Hairuddin; S., Muddath; Anuar, Hazleen; N. A, Jamal (2009)
This project was undertaken to study about rubber toughened polyropylene-kenaf fiber composite. The composite of TPEs reinforced with kenaf fiber was prepared via melt blending method using Thermo Haake 600p internal mixer. TPEs that were used consist of blend of polypropylene (PP) and synthetic rubber (EPDM) AT 50PP/50EPDM ratio. The fiber content was varied from 0-20% volume fraction. TPEs-KF composite was blended at 180 C processing temperature, 40 rpm mixing speed and 10 minutes mixing time. Maleic anhydride-grafted-polypropylene (MAPP) was added at 5% by volume fraction for composite as coupling agent. A study on mechanical properties and fracture mechanism were carried out using tensile testing, impact testing, as well as SEM examination. A tensile property for PP-EPDM-KF composite was increased with the presence of MAPP. The impact strength for PP-EPDM-KF composite was reduced with the increasing of fiber content. SEM micrograph revealed the random orientation of KF, debonding and fiber pull out aggravated the failure and lower the mechanical properties of the composite.